Dual-coding Contrastive Learning Based on the ConvNeXt and ViT Models for Morphological Classification of Galaxies in COSMOS-Web - Shiwei Zhu; Guanwen Fang; Chichun Zhou; Jie Song; Zesen Lin; Yao Dai; Xu Kong (The Astrophysical Journal Supplement Series)
In our previous works, we proposed a machine learning framework named USmorph for efficiently classifying galaxy morphology. In this study, we propose a self-supervised method called contrastive learning to upgrade the unsupervised machine learning (UML) part of the USmorph framework, aiming to improve the efficiency of feature extraction in this step. The upgraded UML method primarily consists of the following three aspects. (1) We employ a convolutional autoencoder to denoise galaxy images and adaptive polar coordinate transformation to enhance the model’s rotational invariance. (2) A pretrained dual-encoder convolutional neural network based on ConvNeXt and a vision transformer is used to encode the image data, while contrastive learning is then applied to reduce the dimension of the features. (3) We adopt a bagging-based clustering model to cluster galaxies with similar features into distinct groups. By carefully dividing the redshift bins, we apply this model to the rest-frame optical images of galaxies in the COSMOS-Web field within the redshift range of 0.5 <  z  < 6.0. Compared to the previous algorithm, the improved UML method successfully classifies 73% of galaxies. Using the GoogLeNet algorithm, we classify the morphology of the remaining 27% of galaxies. To validate the reliability of our updated algorithm, we compared our classification results with other galaxy morphological parameters and found a good consistency with galaxy evolution. Benefiting from its higher efficiency, this updated algorithm is well suited for application in future China Space Station Telescope missions.